2021
DOI: 10.24874/ti.988.10.20.04
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Heat Treatment Analysis on the Wear Behaviour of Al-14.2Si-0.3Mg-TiC Composite using Response Surface Methodology

Abstract: Al-14.2Si-0.3Mg Alloy reinforced with hard phased TiC coarse particulates (10 wt-%) was contrived using the liquid metallurgy route. The so fabricated aluminium metal matrix composites was made to undergo solutionising at 525 0 C for 12 hours in a heat treatment furnace and was subsequently water quenched to room temperature. The developed composite was then kept for age hardening at varying temperatures and time for enhanced tribological properties. A pin on disc Tribometer (ASTM-G99) was utilised to study th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The authors indicated that the presence of 10 wt.% LBWA particles in the composites will provide the highest tensile strength, hardness, and wear resistance. Anilkumar et al [ 91 ] fabricated aluminum metal-matrix composites (AMMC), wherein the Al-14.2Si-0.3Mg alloy was reinforced with coarse TiC particulates of 10 wt.% content. The MMCs were subjected to solutionizing treatment at a temperature of 525 °C for 12 h and were then quenched in water to reach room temperature.…”
Section: Mechanical and Tribological Properties Of Al-based Mmcsmentioning
confidence: 99%
“…The authors indicated that the presence of 10 wt.% LBWA particles in the composites will provide the highest tensile strength, hardness, and wear resistance. Anilkumar et al [ 91 ] fabricated aluminum metal-matrix composites (AMMC), wherein the Al-14.2Si-0.3Mg alloy was reinforced with coarse TiC particulates of 10 wt.% content. The MMCs were subjected to solutionizing treatment at a temperature of 525 °C for 12 h and were then quenched in water to reach room temperature.…”
Section: Mechanical and Tribological Properties Of Al-based Mmcsmentioning
confidence: 99%
“…Shankar et al [27] found the influence of the T6 heat treatment on the tribological behavior of cast Al-12.2Si-0.3Mg-0.2Sr alloy by the response surface methodology. In another similar work, Anilkumar et al [28] checked the heat treatment impact on the wear behavior of Al-14.2Si-0.3Mg-TiC composite, again using the response surface methodology. Their results depicted that by increasing the ageing temperature, the ageing time and the load, a variation was observed in wear properties of the material.…”
Section: Regression Modelmentioning
confidence: 99%
“…Aluminum-based composite materials are among the most widely used metal matrix composite materials as they have a low density, a high strength-to-weight ratio, good electrical and thermal conductivities, a low cost, and a stable performance. They are widely used in the aerospace and automotive industries [1][2][3][4][5]. Modern carbon materials, such as carbon nanotubes (CNTs) and graphene, have a two-dimensional nanometer-size structure, with high strength, a high elastic modulus, and a good thermal conductivity [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%